Orthodontic Elastics: A Multivariable Analysis of YouTubeTM Videos - Alsulaiman AA; Alsulaiman OA; Alkhateeb RI; AlMuhaish L; Alghamdi M; Nassar EA; Almasoud NN (Dove Medical Press, 2024)
Ahmed A Alsulaiman,1 Osama A Alsulaiman,1 Reem I Alkhateeb,2 Luba AlMuhaish,2 Maher Alghamdi,2 Essam A Nassar,1 Naif N Almasoud1 1Department of Preventive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Kingdom of Saudi Arabia; 2College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Kingdom of Saudi ArabiaCorrespondence: Ahmed A Alsulaiman, Department of Preventive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, P. O. Box 1982, Dammam, 31441, Kingdom of Saudi Arabia, Tel +966138574928, Fax +966138572624, Email abalsulaiman@iau.edu.saBackground/Purpose: Whether YouTube videos contain precise and adequate information on certain orthodontic procedures remains unclear. This study aimed to investigate the content and quality of YouTube videos on orthodontic elastics and identify the predictors of high-level content YouTube videos.Materials and Methods: Two hundred YouTube videos were screened for eligibility, and after applying the inclusion criteria, 133 videos were excluded. Student's t-test was used to compare the characteristics, quality parameters, and total content of the low-level and high-level content videos. Chi-square or Fisher's exact tests were implemented to identify the source and content element differences across low-level and high-level content videos. Pearson's correlation coefficients were used to determine the relationship between the total content score, video information and quality index (VIQI), and YouTube characteristics. Stepwise linear multiple regressions with forward selection were used to test the association of the YouTube characteristics and VIQI with the total content score.Results: Among 67 included videos, only 19.4% of videos were classified as high-level content videos. High-level content videos had significantly higher mean number of likes (MD = 4041.7; SD = 4680.7; P-value=0.0068), VIQI score (MD = 4.17; SD = 4.87; P-value=0.0073), and total content score (MD = 4.04; SD = 1.23; P-value=< 0.0001). The adjusted linear regression model demonstrated a significant association between the total content score and VIQI, where 1 unit increase in the VIQI was significantly associated with a 0.16 increase in the total content score (B = 0.16; standard error [SE]=0.04; P = 0.0003). Further, a significant association was observed between the total content score and video duration, where 1 minute increase in the video duration was significantly associated with a 0.15 increase in the total content score (B = 0.15; SE = 0.05; P = 0.008).Conclusion: This study demonstrated that YouTube content quality concerning orthodontic elastics is poor. Thus, future implementation of online visual content provided by certified orthodontists will ensure accurate and thorough information delivery.Keywords: dentistry, orthodontics, social media, youtube, patient compliance